2020
DOI: 10.1371/journal.pone.0237377
|View full text |Cite
|
Sign up to set email alerts
|

Urine metabolomic responses to aerobic and resistance training in rats under chronic unpredictable mild stress

Abstract: Background It is known that bioenergetics of aerobic and resistance exercise are not the same but both can effectively improve depression. However, it is not clear whether and how different types of exercise can influence depression through the same metabolic regulatory system. Metabolomics provides a way to study the correlation between metabolites and changes in exercise and/or diseases through the quantitative analysis of all metabolites in the organism. The objective of this study was to investigate the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…This result corroborates findings from other studies that demonstrated a reduction in pyruvate levels concomitantly with an increase in CRF after moderate to vigorous aerobic training (Henderson et al, 2004 ; LeBlanc et al, 2004 ; Huffman et al, 2014 ). The attenuated production of pyruvate at rest after training has been attributed to the improvement in the cellular energy supply (availability of free ADP and AMP, and inorganic phosphate) and decrease in the glycogenolysis rate, mediated by the decrease in the activity of the pyruvate dehydrogenase complex, which is responsible for decarboxylating pyruvate and supplying the citric acid cycle with Acetyl-CoA (LeBlanc et al, 2004 ; Han et al, 2020 ). Additionally, it is likely that the reduction in the amount of Acetyl-CoA supplied by pyruvate and via glycogenolysis is being offset by the amount derived from the oxidation of fatty acids (Nelson and Cox, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…This result corroborates findings from other studies that demonstrated a reduction in pyruvate levels concomitantly with an increase in CRF after moderate to vigorous aerobic training (Henderson et al, 2004 ; LeBlanc et al, 2004 ; Huffman et al, 2014 ). The attenuated production of pyruvate at rest after training has been attributed to the improvement in the cellular energy supply (availability of free ADP and AMP, and inorganic phosphate) and decrease in the glycogenolysis rate, mediated by the decrease in the activity of the pyruvate dehydrogenase complex, which is responsible for decarboxylating pyruvate and supplying the citric acid cycle with Acetyl-CoA (LeBlanc et al, 2004 ; Han et al, 2020 ). Additionally, it is likely that the reduction in the amount of Acetyl-CoA supplied by pyruvate and via glycogenolysis is being offset by the amount derived from the oxidation of fatty acids (Nelson and Cox, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The method of modeling has been presented previously [ 21 ]. Briefly, 32 male SD rats were randomly divided into 4 groups, with 8 in each group: (1) Blank control group (C), (2) CUMS control group (D), (3) CUMS with endurance exercise group (E), and (4) CUMS with resistance exercise group (R).…”
Section: Methodsmentioning
confidence: 99%
“…It is important to explore the efficacy and understand the mechanisms of various types of exercise interventions for the prevention and treatment of depression as well as other types of health disorders. We have previously examined urine metabolomic responses to endurance and resistance training in rats under chronic unpredictable mild stress (CUMS) [ 21 ]. However, there has been no report to date that has examined the regulatory roles of skeletal muscle metabolites by using metabolomics in relation to the pathophysiological responses to exercise interventions for depression.…”
Section: Introductionmentioning
confidence: 99%
“…According to the methods used in a previous study, the rat model of depression was established by CUMS procedure (17). For the next 28 d (Figure 1), modeling was started at 9 a.m.…”
Section: Chronic Unpredictable Mild Stresses (Cums) Proceduresmentioning
confidence: 99%